Islamisation in the Golden Horde and Anatolia: Some remarks on travelling scholars and texts - A.C.S. Peacock (Université de Provence, 2018)
Abstract: This article examines the intellectual connections between Anatolia and the Golden Horde in the thirteenth and fourteenth centuries. It argues that an exchange of scholars and texts between the two regions had a profound influence on shaping the literary and religious traditions of both. The formation of the literary Turkish language in Anatolia, an increasingly important means for the dissemination of Islam from the end of the thirteenth century, was determined in part by texts and scholars from the Golden Horde. The processes of Islamisation on the Dasht-i Qipchaq and Anatolia were thus closely linked and mutually influential.